2007
DOI: 10.18553/jmcp.2007.13.5.385
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Statins After Hospitalization for Coronary Heart Disease

Abstract: What is already known about this subject• Previous research has shown that as much as 60% of patients with a diagnosis of CHD do not receive lipid-modifying therapy in the ambulatory care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…33 However,Y eet al reported recently that the proportion of patients who received as tatin after aC HD hospitalization increased in each of 4y ears to an average 56% of patients in 2003. 34 Second, we defined continuous treatment broadly.C ontinuous treatment could have been as few as 2p harmacy claims (i.e., 2m onths of treatment) for al ipid-modifying drug in the first 12 months of follow up although the median was 7months and at least 1fill was required in each time period.…”
Section: Nn Discussionmentioning
confidence: 99%
“…33 However,Y eet al reported recently that the proportion of patients who received as tatin after aC HD hospitalization increased in each of 4y ears to an average 56% of patients in 2003. 34 Second, we defined continuous treatment broadly.C ontinuous treatment could have been as few as 2p harmacy claims (i.e., 2m onths of treatment) for al ipid-modifying drug in the first 12 months of follow up although the median was 7months and at least 1fill was required in each time period.…”
Section: Nn Discussionmentioning
confidence: 99%
“…MarketScan has formed the basis of more than 250 peerreviewed publications. 17,18 In compliance with the Health Insurance Portability and Accountability Act, all patient data were de-identified.…”
Section: Study Design and Databasesmentioning
confidence: 99%
“…16 The MarketScan dataset has been used by many other researchers investigating the health and economic burden of CVD. 7,[17][18][19][20][21] Using codes from the International Classification of Diseases, 9 th revision (ICD-9) (Table 1), we identified hospitalizations with a primary or secondary diagnosis of IHD among patients aged 18 to 64 years enrolled in non-capitated health insurance plans. We excluded patients younger than 18 because of the low prevalence of IHD in that age group.…”
Section: Methodsmentioning
confidence: 99%